2019
DOI: 10.1101/777664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endosome-Mediated Epithelial Remodeling Downstream of Hedgehog/Gli Is Required for Tracheoesophageal Separation

Abstract: Highlight bullet points:• The Sox2+ esophagus and Nkx2-1+ trachea arise from the separation of a single foregut tube through a series of cellular events conserved in mouse and Xenopus• Tracheoesophageal morphogenesis initiates with HH/Gli-dependent medial constriction of the gut tube mesenchyme at the Sox2-Nkx2-1 border • The foregut epithelial walls fuse forming a transient septum co-expressing Sox2 and Nkx2-1 • Downstream of HH/Gli Rab11-dependent endosome-mediated epithelial remodeling and localized extrace… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…Immunostaining confirmed that this was indeed a rare Nkx2-1/Sox2+ cell population at the prospective tracheal-esophageal boundary (Fig. 4k, l), which recent studies have demonstrated to be critical in tracheoesophageal morphogenesis 31,32 . In sum, the foregut lineage trajectories predicted from the single-cell transcriptomes represent a valuable resource for further studies.…”
Section: Sox2supporting
confidence: 61%
“…Immunostaining confirmed that this was indeed a rare Nkx2-1/Sox2+ cell population at the prospective tracheal-esophageal boundary (Fig. 4k, l), which recent studies have demonstrated to be critical in tracheoesophageal morphogenesis 31,32 . In sum, the foregut lineage trajectories predicted from the single-cell transcriptomes represent a valuable resource for further studies.…”
Section: Sox2supporting
confidence: 61%
“…The fact that Sox9 was not upregulated in the Dermo1Cre;Foxf1 f/f mutants indicates that Foxf1 does not repress Sox9, which was one possibility suggested by their reciprocal expression patterns. We also found that the Foxg1Cre;Foxf1 f/f mutant foregut failed to separate into a distinct trachea and esophagus ( Figure 4A), consistent with our recent work suggesting that the early lateral plate mesoderm is required for morphogenesis (Nasr et al, 2019).…”
Section: Foxf1 Is Required For Development Of Sox9+ Chondrocytessupporting
confidence: 92%
“…Both Smo f/f and Gli3T Flag/+ mouse models exhibit tracheomalacia and a reduction of Sox9. Previous work showed that Shh -/and Gli2 -/-;Gli3 +/mouse mutant models, which have relatively high levels of Gli3R, displayed tracheomalacia, whereas the Gli2 +/-;Gli3 -/which lack Gli3R, do not (Litingtung et al, 1998;Miller et al, 2004;Nasr et al, 2019;Park et al, 2010). Previous work suggests that some Hedgehog targets may be activated in the loss of GliR; it is also possible that decreased expression of some HH targets is caused by a reduction in GliA rather than an added presence of GliR (Falkenstein and Vokes, 2014).…”
Section: Temporal Roles Of Hh/gli In Tracheal Chondrogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Shh signaling has long been recognized to play an important role in controlling positional cell fates in many developing organs, including the limb, the gut, and the spinal cord ( Jessell, 2000 ; Villavicencio et al, 2000 ; McMahon et al, 2003 ; McGlinn and Tabin, 2006 ; Tickle and Towers, 2017 ; Sagner and Briscoe, 2019 ). Although the effects of Shh on cell behavior have received comparatively less attention, Shh has been shown to influence axon guidance ( Zuñiga and Stoeckli, 2017 ), cell migration ( Gordon et al, 2018 ), mesenchymal cell clustering ( Rao-Bhatia et al, 2020 ), and epithelial remodeling in mice, chicks, frogs, and flies ( Corrigall et al, 2007 ; Escudero et al, 2007 ; Nasr et al, 2019 ; Arraf et al, 2020 ). Depending on the context, proteins in the Shh family can have contrasting effects on epithelial cell behavior, promoting apical constriction in the Drosophila eye ( Corrigall et al, 2007 ; Escudero et al, 2007 ), generating short and flat cells in the neural tube ( Fournier-Thibault et al, 2009 and this work), and inducing tall, pseudostratified cells in the chick coelomic cavity ( Arraf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%